(untitled) (Research, Society and Development, 2021)
The suspension of classroom education due to the new coronavirus pandemic in 2020 led to the search for methodologies applicable to online education. Podcast, for example, is a digital audio file transmitted by social networks to disseminate information, constituting an educational resource in the teaching-learning process. This report aims to present the use of methodologies in the context of remote education for undergraduates in the health field. This is a descriptive study of the experience report type, from the perspective of teachers, students and monitors in the curricular component of Laboratory Diagnostic Methods (MDL), in the period from 14/09 to 19/12/2020, using synchronous and asynchronous moments. During the semester, groups with three or four students developed eight podcasts, an example of standard operating procedure (SOP), dialogued with teachers and monitors in virtual environments and answered their perceptions about the use of these tools for the teaching-learning process in a remote academic calendar. Stand out as answers: 52.6% evaluated the adopted strategies as very good and 42.1% as good; 47.4% used the Anchor program to record and edit the podcast and 73.7% did not feel any difficulties regarding the recording of scripts. For the SOP made, it was committed to carry it out in an extension activity, later. The search for the best methodology was challenging. The podcast proved to be a satisfactory methodology for teaching health in the context of online education for the curricular component (CDM). It is envisaged to socialize the produced podcasts in different communities, in order to popularize the knowledge obtained and their relationships.